Hydrophobic and antibacterial bed sheet using ZnO nanoparticles: A large-scale technique - Febrian Hendra Kurniawan (2022)
Bed sheet is one of the most frequently contaminated medical equipment in the hospital. In this study, an antibacterial poly(vinyl chloride) (PVC) bed sheet coated with zinc oxide nanoparticle (ZnO-NP) was developed using multiple-layer coating technique on a large scale (1 m × 1 m). A number of coating cycles was varied, and the properties of the coated bed sheet were observed for their ZnO concentration. Coated bed sheet was also investigated for its wetting property as well as its antibacterial activity against S. aureus, S. epidermidis, E. coli, and P. aeruginosa. Results showed that bed sheet with 15 cycles of coating had the highest ZnO concentration of 0.17 mg/cm2 and the highest hydrophobicity with the contact angle at 117° ± 0.76. The antibacterial activities and observation under SEM suggested that the coated bed sheet reduced the adherence of both gram-positive and gram-negative bacteria, with ZnO-NP effectiveness being higher on gram-positive compared to gram-negative bacteria. This nanocoating procedure can also be applied to other medical devices that are potentially listed as sources of infection.